2014
DOI: 10.1038/nchem.1894
|View full text |Cite
|
Sign up to set email alerts
|

Short peptides self-assemble to produce catalytic amyloids

Abstract: Enzymes fold into unique three-dimensional structures, which underlie their remarkable catalytic properties. The requirement to adopt a stable, folded conformation is likely to contribute to their relatively large size (> 10,000 Dalton). However, much shorter peptides can achieve well-defined conformations through the formation of amyloid fibrils. To test whether short amyloid-forming peptides might in fact be capable of enzyme-like catalysis, we designed a series of 7-residue peptides that act as Zn2+-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
557
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 555 publications
(596 citation statements)
references
References 38 publications
24
557
2
4
Order By: Relevance
“…7,9−11 To date, amyloid fibers have been functionalized for applications in tissue engineering, 12,13 drug delivery, 14−16 enzyme immobilization, 17 metal nanowires, 18−20 protein films, 21 light-harvesting nanodevices, 8,22 retroviral gene transfer enhancer, 23 environmental carbon dioxide capture, 24 and enzyme-like catalysis. 25 Although first identified as pathological entities, amyloid fibers have evolved in living organisms from prokaryotes to eukaryotes to perform diverse functions, including signal transduction, 26 RNA granule formation, 27 memory persistence, 28 hormone storage, 29 and cell surface adhesion. 30 The distinctive properties of amyloid fibers and their diverse functions in nature suggest that research on amyloid materials could contribute significantly to bio-nanotechnology.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7,9−11 To date, amyloid fibers have been functionalized for applications in tissue engineering, 12,13 drug delivery, 14−16 enzyme immobilization, 17 metal nanowires, 18−20 protein films, 21 light-harvesting nanodevices, 8,22 retroviral gene transfer enhancer, 23 environmental carbon dioxide capture, 24 and enzyme-like catalysis. 25 Although first identified as pathological entities, amyloid fibers have evolved in living organisms from prokaryotes to eukaryotes to perform diverse functions, including signal transduction, 26 RNA granule formation, 27 memory persistence, 28 hormone storage, 29 and cell surface adhesion. 30 The distinctive properties of amyloid fibers and their diverse functions in nature suggest that research on amyloid materials could contribute significantly to bio-nanotechnology.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[20][21][22] Although more challenging, this would carry advantages over redesign approaches: firstly, the designer could select and control all, or at least many of the residues, and so engineer the complete construct predictably; secondly, the resulting proteins could be made to function under conditions away from those required by natural proteins; and finally, success in this area would provide the acid test of our understanding of enzyme structure and function. Towards this fully de novo effort, successful designs of hydrolases have included: the decoration of small protein-folding motifs with His residues; 23,24 the employment of Zn 2+ cations as Lewisacidic cofactors; [25][26][27][28] and the identification of catalytically active proteins in combinatorial libraries of sequences patterned to form to all- or all- protein folds. 29 One of the most productive areas in the de novo design of protein structure has been for coiled-coil assemblies.…”
mentioning
confidence: 99%
“…Several studies have demonstrated that natural amyloidogenic and designed amphiphilic peptides are capable of self-assembling into nanostructures with topographies including fibril, film, nanotube, hydrogel, and liquid crystals (15)(16)(17)(18)(19)(20)(21), and these nanostructures have been used for nanowires, biosensors, 3D culturing, environmental carbon capture, retroviral gene transfer, light harvesting, and catalysis (22)(23)(24)(25)(26). Amyloid fibrils were also hybridized with other nanomaterials such as graphene and DNA origami in hopes of creating new properties and functions (27)(28)(29).…”
mentioning
confidence: 99%